Enhancing Creative Thinking Ability of Students in Probability Topics Through React Learning - Primaningsih, Dyani; Murtafiah, Wasilatul (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2019)
This study aimed to improve creative thinking ability of students through REACT learning strategy approach in probability topics. REACT learning strategy approach has 5 stages, consist of Relating, Experiencing, Applying, Cooperating, and Transferring. The type of research is Classroom Action Research. The study population was twelfth grade students of SMAN 1 Nglames, and the sample used was one class of XII MIA 2 consist of 32 students. The data collection technique uses (1) test scores of students' creative thinking skills which include the initial and final tests, (2) the results of observations during the learning process, (3) the results of interviews with the subject of the interview. Data were analyzed through descriptive analytic techniques. Based on the data analysis, it was found that each component of creative thinking had the following percentage increase in fluency (5.22%), flexibility (8.81%), originality (21.57%), and elaboration (29.29%). The results showed that REACT learning through three stages, namely the initial stage, the core (Relating, Experiencing, Applying, Cooperating, and Transferring), and the closure can improve students' creative thinking skills, especially in the probability topics.